Pengaruh Media Kartu Bilangan Terhadap Kemampuan Kognitif Anak Di TK IT El-Banna Sibuhuan Kecamatan Barumun Kabupaten Padang Lawas - Lisda Khairani Pulungan (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
The aim of this research is to find out: (1) how children's cognitive development at TKIT El – Banna Sibuhuan is, (2) the influence of number card media on children's cognitive abilities at TKIT El – Banna Sibuhuan. This research is quantitative research with the type of experimental research. The research design used a one-group pretest-posttest type pre-experiment. The instruments used consist of observation, documentation and tests. The data analysis technique uses descriptive statistics and carries out a "t" test.The results of the research show that: (1) The implementation of number card media at TKIT El – Banna Sibuhuan is going well. This can be seen from the results of observations during the pretest which obtained an average of 38.81, while at the posttest stage the average observation results obtained were 38.81. 46.68. Based on these results, there was a very significant increase from the pretest observation results to the posttest observation results. (2) The results of the "t" test calculation obtained tcount = 0.262 when compared with ttable at a confidence level of 95% or an error rate of 5% with degrees of freedom (db) = N – k = 16 – 1 = 15 obtained ttable = 2.042. If the value of tcount = 0.262 is compared with ttable = 2.042 then it is known that tcount is smaller than ttable, (0.262<2.042). This means that the proposed hypothesis is accepted as true. This means that there is a significant influence between number card media on children's cognitive abilities at TKIT El – Banna Sibuhuan, Barumun District, Padang Lawas Regency.